PELAKSANAAN PENEMPATAN DAN PERLINDUNGAN TENAGA KERJA INDONESIA (TKI) BERDASARKAN UNDANG-UNDANG NOMOR 39 TAHUN 2004 TENTANG PENEMPATAN DAN PERLINDUNGAN TENAGA KERJA INDONESIA (TKI) DI LUAR NEGERI - Sartika, Yulia; Firdaus, Emilda; Ghafur, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In act number 39 year 2004 on the placement and protection Indonesian workers abroad set provisions regarding development activities on all activities related to the implementation of the placement and protection of Indonesian workers abroad will be undertaken by the government. This seen from case data in body national location and protection of labour Indonesian of year 2014 and 2015 and also cases in general. Target of writing of this skripsi, namely is ; First, Location and protection of labour Indonesian pursuant to law number 39 Year 2004 about location and protection of labour Indonesian beyond The Sea, Both, Constraint in location and protection of labour Indonesian pursuant to law number 39 Year 2004 about location and protection of labour Indonesian beyond the Sea is, Third, Strive performed within location and protection of labour Indonesian pursuant to law number 39 Year 2004 about location and protection of labour Indonesian beyond the sea.This Type Research can be classified in type research of empirical yuridis. Research location is body national location and protection of labour Indonesian. Source of data, in supporting by source of primary data and data source of sekunder, source of data of sekunder consist of three law materials, that is : materials punish primary, materials punish sekunder, materials punish tertier, while data collecting technique is or interview of interview bibliography study and. After gathered data hereinafter in analysis qualitative by using deductive method that is analysing and problems having the character of public later; then in drawing at conclusion peculiarly pursuant to existing theory.From result of research of problem there is fundamental three things able to in concluding is. First, Location and protection of Indonesian labour candidate during the time have walked better but not yet optimal because during the time still many Indonesian labour candidate having an affair so that need the existence of policy of private sector side and government. Both, Constraint in location and protection of labour Indonesia cover : (1) Indonesian labour of nonprocedural (2) ill Indonesian labour or pass away (3) Indonesian labour use double passport. Third, Strive performed within location and protection of Labour Indonesian can through solution by mediasi, solution by litigasi. Suggestion writer, First, The importance of coherent and clear regulation hit duty and also governmental responsibility and side or organizer of private sector to give protection and location to labour Indonesian. Both, the importance of settlement repeat system location of TKI beyond the sea is, Third, The importance of directing of certain institute which given by duty conduct socialization with existence of program pass by quickly sector, program to society about order become Indonesian labour beyond the sea.Keywords : Location - Protection – Indonesian Workers